KUALITAS PELAYANAN DAN FASILITAS FISIK TERHADAP KEPUASAN PESERTA DIDIK (STUDI PADA LP3I COLLEGE PURWAKARTA) - Natalia, Inpresta; Nurhayati, Nurhayati; Apria, Eka (JAB (Jurnal Akuntansi & Bisnis), 2020)
ABSTRACTÂ This study aims to determine the effect of service quality and physical facilities on student statisfaction in educational institutions LP3I College Purwakarta. The research method used is a survey method with descriptive reserach type. This is research was conducted in the city of purwakarta, this study uses primary data, by distributing questionnaries directly to the parties related to the reserach used. Sampling technique in research using Accidental Sampling method with number of samples as much as 100 respondents. The dependent variabel is student statisfaction, while the independent variabel is the quality of service and physical facilities. By using individual analysis, the result of the study conculaded that the quality of services and facilities had a positive and significant effect on student statisfaction. Based on the results of the F test. The reaults of this study indicate the quality of services and physical facilities have a positve and significant effect on student satisfaction. Â Keywords : Service, facilities, student